The Effect of Marketing Mix and Social Media on The Admission Of New Students in Private Higher Education (A Case Study of IIB Darmajaya Bandar Lampung) - Francis Mukemba Mwau; Faurani Santi; Indra Jaya; Anggalia Wibasuri (Prosiding International conference on Information Technology and Business (ICITB), 2020)
Marketing strategies and activities of business marketing in the educational system are limited, much more than in other service and production industries. The components of the marketing mix (product, price, place, promotion, people, process, and physical evidence) can change a firm’s competitive position. Therefore, universities have to compete by creating their distinctive point clearly to the public. Moreover, the competitive situation is crucially the main competitive tool. The method in this study used an explanatory descriptive method to obtain a description of marketing performance using social media, to make the decision of prospective students to choose private universities, and to find the relationship between variables through hypothesis testing from the results of data collection in the field. The result of this study showed that the performance of the marketing mix and the use of social media had a significant effect on the decision of prospective students to choose a college. Furthermore, higher education institutions must continue to use various variables in the marketing mix and increase the use of social media in digital marketing.Keywords:Marketing Mix, Social Media, Consumer Decisions, College, New Student